Sulforaphane response on aluminum-induced oxidative stress, alterations in sperm characterization and testicular histomorphometry in Wistar rats - Babatunde Ogunlade; Sunday Adelakun; Kingsley Iteire (Shahid Sadoughi University of Medical Sciences, 2020)
Background: The exposure of male individual to environmental toxicant is regarded as a channel that results in reduced sperm counts and infertility. Objective: This study investigated the ameliorative response of Sulforaphane (SFN) on Aluminum trichloride (AlCl 3 ) induced testicular toxicity in adult male Wistar rats. Materials and Methods: A total of 32 adult male Wistar rats (180-200 gm between 8-10 wk) were divided into four groups (n = 8/each). Group A) received distilled water orally as placebo; Group B) received 100 mg/kgbw AlCl 3 only orally; Group C) received 100 mg/kgbw AlCl 3 and 100 mg/kgbw SFN orally; and Group D) received 100 mg/kgbw SFN only orally. After 28 days of experiment, animals underwent cervical dislocation, blood serum was obtained for analysis, and testes were harvested for biochemical assays, histology, hormonal profile, and sperm characterization. Results: The sperm parameters showed a significant difference within the AlCl 3 only group compared with the control and SFN only groups (p = 0.02). However, AlCl 3 and SFN co-treatment showed improvement in the motility, viability, and sperm count compared with the AlCl 3 only group (p = 0.02). Furthermore, there was a significant decline in the levels of hormones profile and antioxidant status in AlCl 3 only group compared to the control and SFN only (p = 0.02). The testicular histoarchitecture of the AlCl 3 only group showed shrinkage of seminiferous tubules, spermatogenesis disruption, and empty lumen compared to the control and SFN only groups. Conclusion: The present study revealed the ameliorative response of SFN on AlCl 3 -induced testicular toxicity on serum hormone profiles, antioxidant status, lipid peroxidation, and histomorphometric analysis through oxidative stress.